Characterization of laccase gene StLAC6 and its involvement in the pathogenicity and peroxisome function in Setosphaeria turcica - Ning LIU; Qian-qian ZHANG; Hui JIA; Bin ZHAO; Zi-ping ZHU; Zhi-yan CAO; Jin-gao DONG (Journal of Integrative Agriculture, 2022)
Laccases, as a kind of multicopper oxidase, play an important role in pigment synthesis and growth in fungi and are involved in their interactions with host plants. In Setosphaeria turcica, 9 laccase-like multicopper oxidases have been identified, and StLAC2 is involved in the synthesis of the melanin that accumulates in the cell wall. The function of another major laccase gene, StLAC6, was studied here. The knockout of StLAC6 had no effect on the growth, morphology or invasion ability of S. turcica, but the morphology and function of peroxisomes of knockout mutants were abnormal. The knockout of the StLAC6 gene resulted in increased contents of phenolic compounds and melanin and the sensitivity to fungicides increased compared with wild type strains. In the mutants of StLAC6, there is a significant change of the expression levels of other laccase genes. This study provides a new insight into laccase functions and the relationship of the laccase gene family in plant pathogenic fungi.